Imaginary part of microscopic optical potential at negative energies - Tam Do Quang; Vinh Phu Nguyen; Minh Hoa Nguyen; Hong Nga Nguyen Thi; Quynh Nhu Tran Duy; Nhan Hao Tran Viet; Le Uyen Vo (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên, 2023)
In this paper, we calculate the diagonal contributions W(R, s = 0) of the imaginary part of the microsopic optical potential at negatives energies, where W(R, s) = Σlj(2j+1)/4π Im∆Σlj(r, r′, ω), with R = 1/2.(r + r′) corresponding to the radius and shape of Im∆Σ, and s = r - r′. To do it, the microscopic optical potential has been calculated by using the nuclear structure approach which is based on the Green function method. The coupling between the particle and collective phonon has been performed to calculate the dynamic part of the optical potential. It has been found that the imaginary part at negative energies is very small as expected. The calculated W(R, 0) is maximum on the surface and deacreases to zero in the interior.